The Combined Effect of Q-Switched Nd:YAG Laser (532 Nm) and Safranin O on the Growth of Pseudomonas Aeruginosaand its Susceptibilityto Antibiotics and Pyocyanin Production - Abbas, Hanan M.; Maki, Amel M.; Kandala, Nuha (Iraqi Journal of Laser, 2019)
Twenty five samples out of sixty wound swabs taken from burn patients were identified as P. aeruginosabacteria by conventional methods. Antibiotics susceptibility tests were performed against thirteen antibiotics. P. aeruginosa samples were treated with 0.5 mg/ml of Safranin O solution then irradiated with 532nm Q-switched Nd:YAG laser at four energy densities (0.324, 0.704, 1.380, and 1.831 J/cm2) for different times of 5, 8 and 11 minutes with 5Hz repetition rate. The viability, susceptibility to antibiotic and production of pyocyanin were determined before and after irradiation. The results showed that the number of CFU/ml of P. aeruginosa decreased with increasing the dose of irradiation. Complete killing of cells was observed at 1.831 J/cm2 energy density for different times )5, 8 and 11 minutes(. The susceptibility of P. aeruginosato antibiotics increased with increasing the dose of irradiation, especially to Oxacillin and Azithromycin antibiotics, except in the case of Ceftazidime, where no variation in the susceptibility at any dose was observed. No change was observed in the production of pyocyanin.